Britain and the Netherlands - Duke, A. C. author. aut Link
VIII, 256 p. 1 illus.
Keywords: War has ever exercised a great appeal on men's minds. Oscar Wilde's witticism notwithstanding this fascination cannot be attri buted simply to the wicked character of war. The demonic forces released by war have caught the artistic imagination, while sages have reflected on the enigmatic readiness of each new generation to wage war, despite the destruction, disillusion and exhaustion that war is known to bring in its train. If there never was a good war and a bad peace why did armed conflicts recur with such distressing regularity? Was large-scale violence an intrinsic condition of Man? The answers given to such questions have differed widely: it has even been suggested that the states of war and peace are not as far removed from one another as is usually supposed. The causes of war and the interaction between war and society have long been the subject of philosophical enquiry and historical analysis. Accord ing to Thucydides no one was ever compelled to go to war; Cicero remarked how dumb were the laws in time of war, while Clausewitz's profound observation concerning the affinity between war and politics has become almost a commonplace. War being the severest test a society or state can experience historians have naturally been concerned to investigate their rela tionship.